If it's not what You are looking for type in the equation solver your own equation and let us solve it.
15-5x+7x=x+15-3x
We move all terms to the left:
15-5x+7x-(x+15-3x)=0
We add all the numbers together, and all the variables
-5x+7x-(-2x+15)+15=0
We add all the numbers together, and all the variables
2x-(-2x+15)+15=0
We get rid of parentheses
2x+2x-15+15=0
We add all the numbers together, and all the variables
4x=0
x=0/4
x=0
| 4n-3=-2n-1 | | 6+18x=18x-18 | | 3x-5=x^2+5x-13 | | 8t-(6t-1)-2=5 | | 1x-11=-5 | | 1-v-v=v-5-2v | | 5x+8=-62-5xx= | | 6x-4=-9x | | 7+2x=x-(5-4x) | | 9+17x-6=7x+111-2x | | 4(n+6)=36 | | 3x(10x-15)=180 | | -2=(3x+11)/2 | | 7x+10=4-x | | 70x-40=10(7x-4) | | x+x83=231 | | 5.5x-17=-2 | | 3x+13+40=360 | | 192x-96=16(12x-6) | | 7+5x=-3+2x+5x | | 2x+10+2x+10+x+x=36 | | Y=2/3(x)+10 | | 2-10d=10-9d | | 32x+82=32x+25 | | -2x-7×3x=10 | | Y=2/3(x)-10 | | 12x-16=38 | | (1/3)x+4=16 | | 3x-69=2 | | 1/4a=3/4 | | 9x2+39x-30=0 | | 116=7y+6=4y |